Upaya Meningkatkan Pemahaman Konsep Penjumlahan dan Pengurangan melalui Media Konkret pada Siswa Kelas II SD - Abdul Majid; Syarifuddin Syarifuddin (ANWARUL, 2026)
Although mathematics learning in elementary schools has been widely developed, conceptual understanding of addition and subtraction among second-grade students remains a common problem, particularly because of students’ low ability to understand the meaning of arithmetic operations and their tendency to memorize without deep conceptual understanding. This study aimed to improve conceptual understanding of addition and subtraction through the use of concrete media among second-grade elementary school students. This study used a quantitative approach with a Classroom Action Research (CAR) design conducted in two cycles. The research subjects were 20 second-grade elementary school students selected purposively. Data were collected through learning outcome tests, student activity observation sheets, and documentation, and were then analyzed using quantitative descriptive analysis to examine improvements in learning outcomes in each cycle. The results showed that the use of concrete media, such as real objects, counting blocks, and number cards, was able to improve students’ conceptual understanding of addition and subtraction. This was evident from the increase in students’ average score from 60 in Cycle I to 80 in Cycle II, as well as the increase in learning mastery from 50% to 85%. In addition, students’ activity and participation in learning also increased. These findings confirm that concrete media play an important role in helping students understand mathematical concepts in a more concrete and meaningful way. The conclusion of this study shows that the use of concrete media can serve as an effective and student-centered learning strategy for improving conceptual understanding of addition and subtraction in the lower grades of elementary school.